The Role of Check-in Counter Division in Passenger and Baggage Profiling Service at Sriwijaya Air Soekarno-Hatta International Airport - Almas Sugiarti, Afifah (Ann Publisher, 2023)
This study aims to determine the role of the check-in counter division in passenger and baggage profiling services at Sriwijaya Air Soekarno Hatta International Airport. In this study, the authors used descriptive research methods with a qualitative approach. The results of this study indicate that the role of the check-in counter division is very important in the smooth service process at the time of departure and in the service of profiling passengers and baggage, in the implementation of check-in services it is a procedure that must be carried out in every check-in service process. Therefore, the check-in counter division should pay attention to the quality of service that will be provided to each passenger in the implementation of passenger and baggage profiling services at check-in based on the dimension of service quality initiated by Kotler, namely Tangible dimensions, Reability, Responsiveness, Assurance, and Emphaty and its indicators. It can be concluded that there is a dimension of service quality Tangible, Reability, Responsiveness, Assurance, and Emphaty in the implementation of check-in and profiling services in the check-in counter division of Sriwiijaya Air.